Composite hydrogel as well as preparation method and application thereof
By adding luteolin nanoparticles and biological stem cells to the composite hydrogel of sodium alginate and chitosan matrix, the existing wound dressings have poor absorption and permeability in complex wound management, and the results show that the absorption and permeability of existing wound dressings are solved. The problems of strong sensitivity and difficulty in fixing have achieved efficient wound healing effect.
Patent Information
- Application Number
- CN202411610349.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-11
AI Technical Summary
In the complex wound management, existing wound dressings have problems such as poor fluid absorption, poor breathability, strong sensitization and difficulty in fixing, resulting in poor wound healing ability.
A composite hydrogel with sodium alginate and chitosan as the matrix was added, luteolin nanoparticles and loaded biological stem cells were added to form a composite hydrogel with anti-inflammatory, antibacterial and wound healing functions.
The introduction of luteolin nanoparticles enhances antibacterial, anti-inflammatory and antioxidant biological activities, while the existence of biological stem cells promotes tissue regeneration and repair, allowing the composite hydrogel to promote wound healing while antibacterial and anti-inflammatory, significantly Improves the efficiency and quality of wound healing.
Smart Images

Figure CN119405877A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technology, and in particular to a composite hydrogel and a preparation method and application thereof. Background Art
[0002] Wound healing, as the body's natural process of repairing damaged tissue, is a complex and highly finely regulated sequence of biological events, covering multiple continuous and partially overlapping stages such as hemostasis, inflammatory response, proliferation, epithelialization, maturation, and scar tissue remodeling. However, in clinical practice, the wound healing process is often disturbed by multiple factors, such as infection, excessive inflammatory activation, and oxidative stress. Especially in chronic wounds, endogenous or exogenous factors can lead to an imbalance in the inflammatory regulation mechanism, which not only delays the wound healing process, but may also cause serious complications, thereby increasing the patient's pain and medical burden.
[0003] Luteolin (Lu), as a natural flavonoid compound, has multiple biological activities such as antibacterial, anti-inflammatory and antioxidant. It can not only inhibit the growth of pathogens and reduce inflammatory responses, but also protect cells from oxidative stress damage through antioxidant effects. It is considered to be an ideal candidate drug for improving the wound healing process. However, its low solubility and bioavailability limit its application in clinical practice.
[0004] Adipose-derived Mesenchymal Stem Cells (ADSCs) are multipotent stem cells derived from adipose tissue. As star cells in the field of regenerative medicine and tissue engineering, they show great therapeutic potential due to their powerful paracrine effects, self-replication ability and multidirectional differentiation potential. They can secrete a variety of bioactive factors, which play an important role in promoting wound healing, angiogenesis and tissue regeneration. However, although stem cells and exosomes can promote wound healing and regeneration, they lack a mechanism to effectively protect the wound surface, making the wound prone to infection or secondary injury. In order to overcome this problem, dressing-assisted means are currently used. Traditional wound dressings mainly include gauze and sponges. Although they provide physical protection to a certain extent, their limitations are obvious: poor absorption of exudate, poor air permeability, strong sensitization, and usually require additional auxiliary materials for fixation. These limit their application effect in complex wound management, resulting in poor wound healing ability. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a composite hydrogel and a preparation method and application thereof. The composite hydrogel uses sodium alginate and chitosan as a matrix, adds luteolin nanoparticles as a drug, and loads biological stem cells at the same time, and has the functions of anti-inflammatory, antibacterial and promoting wound healing.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A composite hydrogel comprises a gel matrix and a drug component loaded in the gel matrix; the gel matrix comprises sodium alginate and chitosan; the drug component comprises luteolin nanoparticles and biological stem cells.
[0008] Sodium alginate is a natural polysaccharide polymer with good biocompatibility and biodegradability. When used as a matrix material for hydrogels, it can form a stable gel structure, increase the viscosity and stability of the hydrogel, and sodium alginate also has strong hydrophilicity, which can absorb wound exudate, reduce inflammatory response, promote cell migration, and thus accelerate wound healing;
[0009] Chitosan is an alkaline linear polysaccharide with anti-inflammatory, antioxidant and antibacterial properties, and has good biocompatibility, non-toxicity, biodegradability and bioadhesion. When used as a matrix material for hydrogels, chitosan can be combined with other natural polymer materials (such as sodium alginate, hyaluronic acid, etc.) to form hydrogels with specific functions.
[0010] Luteolin nanoparticles are nanoparticles prepared from luteolin, which improve the water solubility and stability of luteolin, increase its bioavailability, and ensure its multiple biological activities of antibacterial, anti-inflammatory and antioxidant. Loading luteolin nanoparticles in hydrogel can achieve controlled release of drugs and improve the therapeutic effect.
[0011] Biological stem cells have the ability to self-renew and differentiate into a variety of cell types, which can promote tissue regeneration and repair and have a wide range of applications in regenerative medicine and tissue engineering;
[0012] According to the above technical means, the present application provides a stable and biocompatible carrier by combining a gel matrix formed by sodium alginate and chitosan, providing a solid foundation for the subsequent loaded drug components, and forms a composite hydrogel with good absorption and exudate absorption capacity, air permeability, low sensitization and convenient fixation by loading luteolin nanoparticles and biological stem cells on the carrier, thereby achieving the dual therapeutic effects of drugs and cells. The introduction of luteolin nanoparticles enhances the antibacterial, anti-inflammatory and antioxidant biological activities, while the presence of biological stem cells promotes tissue regeneration and repair, so that the composite hydrogel has good effects in promoting wound healing while having antibacterial and anti-inflammatory properties. The synergistic effect of the two significantly improves the efficiency and quality of wound healing, provides an innovative and efficient solution for complex wound management, improves the therapeutic effect, and has important clinical significance and broad market application prospects.
[0013] A method for preparing the composite hydrogel comprises the following steps:
[0014] S1. Dissolve chitosan in acetic acid solution to obtain solution A.
[0015] S2, dissolving sodium alginate in double distilled water to obtain solution B;
[0016] S3, dissolving genipin in an ethanol solution to obtain a solution C;
[0017] S4, taking solution A, solution B and solution C, stirring and mixing, and standing at a constant temperature of 20-40° C. and away from light for 24 hours to obtain chitosan / sodium alginate hydrogel;
[0018] S5, collecting and resuspending the biological stem cells of the 3rd to 6th generations of logarithmic growth and adding them to the chitosan / sodium alginate hydrogel, and standing them at a constant temperature of 20 to 40° C. in the dark for 24 hours to obtain the chitosan / sodium alginate hydrogel carrying stem cells;
[0019] S6. Coat luteolin nanoparticles on the surface of chitosan / sodium alginate hydrogel carrying stem cells, and let stand for 2 hours to form a nanoparticle film, thereby obtaining a composite hydrogel loaded with nanoparticles and stem cells.
[0020] According to the above technical means, genipin, as an excellent natural biological cross-linking agent, plays a key cross-linking role between chitosan and sodium alginate, and can react with chitosan (with natural polycationic properties) and sodium alginate (with anionic properties) in the form of single molecules and multiple molecules to form a stable cross-linked structure, thereby enhancing the structural stability and biocompatibility of chitosan / sodium alginate hydrogel;
[0021] This application combines chitosan and sodium alginate through genipin to form a stable matrix, and further loads biological stem cells and luteolin nanoparticles, thereby achieving the dual therapeutic effects of drugs and cells. It not only significantly improves the antibacterial, anti-inflammatory, antioxidant and tissue regeneration capabilities of the hydrogel, but also optimizes its absorption of exudate, air permeability and low allergenicity. The preparation method is simple, the reaction conditions are mild, and the reagents used are green and pollution-free, providing an efficient, innovative and biocompatible solution for complex wound management.
[0022] Furthermore, the method for preparing luteolin nanoparticles in step S6 comprises the following steps:
[0023] Place polyvinyl alcohol in double distilled water and dissolve it in a constant temperature water bath at 80°C to obtain a solution D with a concentration of 5 mg / mL;
[0024] Luteolin and polyphenylene sulfide-polyethylene glycol were placed in 1 mL of ethanol / chloroform solution and sonicated until completely dissolved to obtain solution E with a concentration of 2.14 mg / mL;
[0025] Solution E was quickly added to solution D, and ultrasonic emulsification was performed for 10 minutes. The ethanol and chloroform were removed by rotary evaporation for 10 minutes, and the solution was centrifuged at 5000 r / min for 5 minutes to obtain luteolin nanoparticles.
[0026] According to the above technical means, luteolin, as a natural flavonoid compound, has multiple biological activities such as antibacterial, anti-inflammatory and antioxidant, but its low solubility and bioavailability limit its application in clinical practice. The preparation method of the present application is simple, the reaction conditions are mild, and the reagents used are green and pollution-free. By combining the solubility characteristics of polyvinyl alcohol and the chemical properties of luteolin, luteolin nanoparticles are prepared, and the luteolin nanoparticles have good stability.
[0027] Furthermore, the viscosity of chitosan in solution A in step S1 is 200-400 mPa.s, and the concentration is 200 mg / mL.
[0028] Furthermore, the viscosity of the sodium alginate in the solution B in step S2 is 200-400 mPa.s, and the concentration is 200 mg / mL.
[0029] Furthermore, the concentration of genipin in solution C in step S3 is 5 mg / mL.
[0030] Furthermore, in step S4, the volume ratio of solution A, solution B and solution C is 5:10:1.
[0031] Furthermore, the light-proof standing temperature in step S4 and step S5 is 37° C.
[0032] Furthermore, the biological stem cells are mouse adipose mesenchymal stem cells.
[0033] An application of the composite hydrogel in preparing a repair-promoting medical dressing.
[0034] Beneficial effects achieved by the present invention:
[0035] The present invention provides a stable and biocompatible carrier by combining a gel matrix formed by sodium alginate and chitosan, providing a solid foundation for the subsequent loaded drug components, and forms a composite hydrogel with good absorption and exudate absorption capacity, air permeability, low sensitization and convenient fixation by loading luteolin nanoparticles and biological stem cells on the carrier, thereby achieving the dual therapeutic effects of drugs and cells. The introduction of luteolin nanoparticles enhances the antibacterial, anti-inflammatory and antioxidant biological activities, while the presence of biological stem cells promotes tissue regeneration and repair, so that the composite hydrogel has good effects in promoting wound healing while having antibacterial and anti-inflammatory properties. The synergistic effect of the two significantly improves the efficiency and quality of wound healing, provides an innovative and efficient solution for complex wound management, improves the therapeutic effect, and has important clinical significance and broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a transmission electron microscopy analysis diagram of the luteolin nanoparticles of the present invention;
[0037] Figure 2 This is a scanning electron microscope analysis image of the composite hydrogel of the present invention after freeze-drying for 24 hours;
[0038] Figure 3 This is a graph showing the live / dead cell staining results in the composite hydrogel of the present invention;
[0039] Figure 4 This is a graph showing the effect of the present invention on the proliferation of mouse fibroblasts (L929);
[0040] Figure 5 This is a graph showing the anti-inflammatory effect of the present invention on the inflammatory factor interleukin-1β (IL-1β);
[0041] Figure 6 This is a graph showing the anti-inflammatory effect of the present invention on the inflammatory factor interleukin-6 (IL-6);
[0042] Figure 7 This is a graph showing the anti-inflammatory effect of the present invention on the inflammatory factor tumor necrosis factor-α (TNF-α);
[0043] Figure 8This is a comparison chart of wound sizes on days 0, 3, 7, 14, and 21 of Example 5 of the present invention;
[0044] Fig. 9 This is a statistical chart of wound size at days 0, 3, 7, 14 and 21 of Example 5 of the present invention;
[0045] Fig.10 This is a diagram showing the results of hematoxylin-eosin staining (H&E) of wound tissue in Example 5 of the present invention;
[0046] Fig.11 This is a Masson trichrome staining result of wound tissue in Example 5 of the present invention;
[0047] Fig.12 This is a diagram showing the results of immunohistochemical staining of myeloperoxidase (MPO) in wound tissue in Example 5 of the present invention;
[0048] Fig.13 This is a diagram showing the results of immunohistochemical staining of vascular endothelial growth factor (VEGF) in wound tissue of Example 5 of the present invention. DETAILED DESCRIPTION
[0049] In order to better understand the technical scheme of the present invention, achieve the purpose and beneficial effect, the present invention is further specifically described by the following examples, but it should not be understood as limiting the present invention. Some non-essential improvements and adjustments made by those skilled in the art according to the above invention content are also considered to fall within the protection scope of the present invention. The experimental methods for which specific conditions are not indicated in the embodiments are usually carried out under conventional conditions or under the conditions recommended by the reagent manufacturer. Unless otherwise specified, the reagents and equipment used in the present invention are conventional reagents and equipment in the art.
[0050] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0051] Example 1: Preparation of Luteolin Nanoparticles
[0052] 1. Experimental Materials
[0053] Luteolin (TargetMol, USA), polyphenylene sulfide-polyethylene glycol (Xi’an, Ruixi), polyvinyl alcohol (Aladdin, Shanghai), chloroform, ethanol (Wansheng Chuandong, Chongqing).
[0054] 2. Experimental methods
[0055] The specific steps include:
[0056] Under sterile conditions, 1.5 g of polyvinyl alcohol was placed in 300 mL of double distilled water, and dissolved in a constant temperature water bath at 80°C to obtain a solution D with a concentration of 5 mg / mL, which was then frozen at 4°C for later use;
[0057] 2.14 mg of luteolin and 15 mg of polyphenylene sulfide-polyethylene glycol were placed in 1 mL of ethanol / chloroform (ethanol:chloroform = 3:17) solution, and ultrasonicated until completely dissolved to obtain a solution E with a concentration of 2.14 mg / mL, which was placed in a 4°C environment for freezing and later use;
[0058] 6 mL of solution D was taken as the aqueous phase and solution E was taken as the organic phase. The organic phase solution E was quickly added to 6 mL of the aqueous phase solution D. Ultrasonic emulsification was performed for 10 min, followed by rotary evaporation for 10 min to remove ethanol and chloroform. Finally, centrifugation was performed at 5000 r / min for 5 min to obtain luteolin nanoparticles.
[0059] The luteolin nanoparticles were diluted 500 times and then analyzed by transmission electron microscopy.
[0060] 3. Experimental results
[0061] like Figure 1 As shown, luteolin nanoparticles are nearly round particles with good dispersibility and formability.
[0062] Example 2: Preparation of composite hydrogel
[0063] 1. Experimental Materials
[0064] Chitosan, sodium alginate, genipin (Aladdin, Shanghai), ethanol (Wansheng Chuandong, Chongqing), inverted fluorescence microscope, live cell / dead cell double staining kit (Beibo, Shanghai), mouse adipose-derived mesenchymal stem cells, and luteolin nanoparticles prepared under the conditions of Example 1.
[0065] 2. Experimental methods
[0066] This experiment was carried out under sterile conditions and included the following steps:
[0067] S1. Take 1 g of chitosan and fully dissolve it in 50 mL of 2% acetic acid solution to obtain solution A, which is placed in a 4°C environment and frozen for later use;
[0068] S2, take 1g of sodium alginate and fully dissolve it in 50mL of double distilled water to obtain solution B, and place it in a 4°C environment for freezing;
[0069] S3, take 15 mg of genipin and fully dissolve it in 3 mL of ethanol solution to obtain solution C, and place it in a freezer at a temperature of 4°C for later use;
[0070] S4, take 1 mL of solution A and 2 mL of solution B, add them to 200 μL of solution C, stir and mix, and keep at 37°C in the dark for 24 h to obtain chitosan / sodium alginate hydrogel;
[0071] S5. Take the 3rd to 6th generation mouse adipose-derived mesenchymal stem cells from logarithmically growing cells. After 90 minutes of preparing chitosan / sodium alginate hydrogel, collect and resuspend the mouse adipose-derived mesenchymal stem cells and add them to chitosan / sodium alginate hydrogel. Each chitosan / sodium alginate hydrogel is loaded with 2×10 6 The stem cells were placed in a constant temperature and dark environment at 37°C for 24 hours to obtain a chitosan / sodium alginate hydrogel loaded with stem cells.
[0072] S6, coating luteolin nanoparticles on the surface of chitosan / sodium alginate hydrogel carrying stem cells, and letting it stand for 2 hours to form a nanoparticle film, thereby obtaining a composite hydrogel loaded with nanoparticles and stem cells;
[0073] The composite hydrogel was freeze-dried for 24 hours and then subjected to electron microscopy scanning analysis. The live / dead cells of the stem cells in the composite hydrogel were stained using a live cell / dead cell double staining kit and observed and analyzed at 24 hours, 48 hours, and 72 hours.
[0074] 3. Experimental results
[0075] like Figure 2 As shown, the composite hydrogel is a loose and dense porous structure with good mechanical properties and stability; Figure 3 As shown, it can be observed that after 72 hours, a large number of living cells (green fluorescence) are still alive, indicating that chitosan / sodium alginate hydrogel can be used as a scaffold for mouse adipose-derived mesenchymal stem cells, and loading mouse adipose-derived mesenchymal stem cells can support the survival and proliferation of stem cells.
[0076] Example 3: Proliferation assay
[0077] 1. Experimental Materials
[0078] Luteolin nanoparticles prepared under the conditions of Example 1, chitosan / sodium alginate hydrogels prepared under the conditions of Example 2, and composite hydrogels loaded with nanoparticles and stem cells, mouse fibroblasts (L929), DMEM culture medium (Gibco, USA), PBS phosphate buffer (Dingguo Changsheng, Beijing), CCK-8 cell proliferation toxicity kit (MedChem Express, USA).
[0079] 2. Experimental methods
[0080] The mouse fibroblasts of passage 3-4 were collected and counted, with 2×10 5The cells were seeded in a 96-well plate, and four experimental groups (control group, luteolin nanoparticle group, chitosan / sodium alginate hydrogel group, composite hydrogel group loaded with nanoparticles and stem cells) and duplicate wells were set up; incubated in a constant temperature incubator at 37°C and 5% CO2 for 12 hours, the original culture medium was aspirated, and the cells were washed 3 times with PBS, and then the culture medium containing the above experimental groups was added, and incubated for 24, 48, and 72 hours. The CCK-8 cell proliferation toxicity kit was added to the DMEM basal culture medium at a ratio of 1:10 and mixed evenly. The original culture medium was aspirated at 24, 48, and 72 hours, and 200 μL / well was added to the 96-well plate, and incubated at 37°C and 5% CO2 for 2 hours. The absorbance (OD) value at 450 nm was detected using an enzyme reader to observe the proliferation of mouse fibroblasts.
[0081] 3. Experimental results
[0082] like Figure 4 As shown, the composite hydrogel loaded with luteolin nanoparticles and mouse adipose-derived mesenchymal stem cells was non-toxic and could promote cell proliferation.
[0083] Example 4: Anti-inflammatory test
[0084] 1. Experimental Materials
[0085] Luteolin nanoparticles prepared under the conditions of Example 1, chitosan / sodium alginate hydrogel prepared under the conditions of Example 2, and composite hydrogel loaded with nanoparticles and stem cells, lipopolysaccharide LPS (Solaibao, Beijing), ELISA kit (Aimeng Youning, Shanghai), and mouse mononuclear macrophage leukemia cells RAW264.7.
[0086] 2. Experimental methods
[0087] Model construction: Both the model group and the experimental group were treated with 1000 ng / mL LPS for 24 h to induce RAW264.7 to establish a cell inflammatory injury model. The model group did not receive any intervention, while the experimental group was treated with LPS and drugs (luteolin nanoparticle group, chitosan / sodium alginate hydrogel, composite hydrogel loaded with nanoparticles and stem cells) were added and incubated at 37°C and 5% CO2 for 24 h.
[0088] Treatment: The supernatants of the model group and experimental group were collected and centrifuged at 3000 r / min at 4°C for 20 min to remove cell debris and impurities, and the supernatants were stored at -80°C;
[0089] ELISA kits were used to quantitatively detect the inflammatory factors IL-1β, IL-6, and TNF-α in the supernatant of the above cells.
[0090] 3. Experimental results
[0091] like Figure 5, Figure 6 and Figure 7 As shown, the content of inflammatory factors in the supernatant was determined by ELISA kit. Compared with the model group, the experimental groups could significantly inhibit the release of proinflammatory cytokines IL-1β, IL-6 and TNF-α, and reduce the inflammatory response. The experimental group with the addition of composite hydrogel loaded with nanoparticles and stem cells had the best inhibitory effect.
[0092] Example 5: Treatment test of composite hydrogel on skin wound
[0093] 1. Experimental Materials
[0094] Luteolin nanoparticles prepared under the conditions of Example 1, chitosan / sodium alginate hydrogel prepared under the conditions of Example 2, chitosan / sodium alginate hydrogel loaded with luteolin nanoparticles only, and composite hydrogel loaded with nanoparticles and stem cells, SD rats (Sichuan Weitong Lihua Experimental Animal Technology Co., Ltd.), and Staphylococcus aureus.
[0095] 2. Experimental methods
[0096] SD male rats weighing 180-220 g were selected as experimental subjects and fed with 40% high-fat diet for one week. After the rats adapted to the environment, they were used for subsequent experiments.
[0097] First, a 10 mm × 10 mm full-thickness skin defect was constructed on the back of the rats, and the defect area was infected with 20.0 μL of Staphylococcus aureus suspension (1×108 CFU / mL). The model was successfully established 6 hours after infection, and then the rats were divided into groups for treatment; the control group did not receive any treatment, and the experimental group was treated as follows:
[0098] The nanoparticle group used luteolin nanoparticles with a concentration of 128 μg / mL and a volume of 200 μL to apply on the wound surface; the hydrogel-loaded nanoparticle group used a whole piece of chitosan / sodium alginate hydrogel loaded with luteolin nanoparticles and applied to the wound surface, and fixed with a sterile dressing; the hydrogel-loaded nanoparticle and stem cell group used a whole piece of chitosan / sodium alginate hydrogel loaded with stem cells and nanoparticle film, and fixed with a sterile dressing;
[0099] The control group and the experimental group were photographed and the wound sizes were recorded on the 0th, 3rd, 7th, 14th and 21st days of treatment, and the new skin tissue was cut off on the 3rd, 7th, 14th and 21st days for hematoxylin-eosin staining (HE) and Masson's trichrome staining. On the 3rd day, the new skin tissue was cut off for myeloperoxidase (MPO) immunohistochemical staining; on the 7th day, the new skin tissue was cut off for VEGF immunohistochemical staining.
[0100] 3. Experimental results
[0101] like Figure 8 As shown, compared with the control group, the experimental group has a better ability to promote wound repair, among which the composite hydrogel group loaded with nanoparticles and stem cells has the best therapeutic effect, and the wound area is significantly reduced;
[0102] like Fig. 9 As shown, by calculating and comparing different wound areas, it can be seen that compared with other groups, the composite hydrogel group loaded with nanoparticles and stem cells has the best wound repair ability, and the wound healing rate can reach 97% at 14 days;
[0103] like Fig.10 As shown, by comparing the wound HE staining results of the control group and the experimental group, it was shown that: in the early stage of treatment, compared with the control group, the experimental group had more uniform and dense ECM deposition; in the late stage of treatment, compared with the control group, the wound healing speed of the experimental group was accelerated, with a large number of uniform and dense ECM depositions and newly generated sebaceous glands and hair follicles, and the composite hydrogel group loaded with nanoparticles and stem cells could also see obvious newly formed dermis, indicating that the wound repair effect was better;
[0104] like Fig.11 As shown, by comparing the wound HE staining results of the control group and the experimental group, it was shown that: in the late stage of treatment, compared with the control group, the experimental group showed a clear red epidermis and higher collagen deposition, among which the collagen deposition in the composite hydrogel group loaded with nanoparticles and stem cells was the most significant, indicating that the experimental group can promote the production of collagen in the remodeling period, thereby accelerating wound healing;
[0105] like Fig.12 As shown, by comparing the MPO immunohistochemical staining results of the wounds of the control group and the experimental group, it was shown that: compared with the control group, the expression of MPO in the wound tissue of the experimental group was relatively reduced, especially in the hydrogel-loaded nanoparticles and stem cell groups, which was significantly reduced, indicating that the experimental group can inhibit the infiltration of neutrophils during the inflammatory period and thus accelerate wound healing;
[0106] like Fig.13 As shown in the figure, by comparing the VEGF immunohistochemical staining results of the wounds in the control group and the experimental group, it was shown that: compared with the control group, the expression of VEGF in the wound tissue of the experimental group was relatively increased, especially the expression levels of the hydrogel-loaded nanoparticles and stem cell groups were the highest, indicating that the experimental group can promote the formation of new blood vessels in the proliferative period and thus promote wound repair.
[0107] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A composite hydrogel, characterized in that: The invention comprises a gel matrix and a drug component loaded in the gel matrix; the gel matrix comprises sodium alginate and chitosan; and the drug component comprises luteolin nanoparticles and biological stem cells.
2. A method for preparing the composite hydrogel according to claim 1, characterized in that: The following steps are involved: S1. Dissolve chitosan in acetic acid solution to obtain solution A. S2, dissolving sodium alginate in double distilled water to obtain solution B; S3, dissolving genipin in an ethanol solution to obtain a solution C; S4, taking solution A, solution B and solution C, stirring and mixing, and standing at a constant temperature of 20-40° C. and away from light for 24 hours to obtain chitosan / sodium alginate hydrogel; S5, collecting and resuspending the biological stem cells of the 3rd to 6th generations of logarithmic growth and adding them to the chitosan / sodium alginate hydrogel, and standing them at a constant temperature of 20 to 40° C. in the dark for 24 hours to obtain the chitosan / sodium alginate hydrogel carrying stem cells; S6. Coat luteolin nanoparticles on the surface of chitosan / sodium alginate hydrogel carrying stem cells, and let stand for 2 hours to form a nanoparticle film, thereby obtaining a composite hydrogel loaded with nanoparticles and stem cells.
3. The method for preparing the composite hydrogel according to claim 2, characterized in that: The method for preparing luteolin nanoparticles in step S6 comprises the following steps: Place polyvinyl alcohol in double distilled water and dissolve it in a constant temperature water bath at 80°C to obtain a solution D with a concentration of 5 mg / mL; Luteolin and polyphenylene sulfide-polyethylene glycol were placed in 1 mL of ethanol / chloroform solution and sonicated until completely dissolved to obtain solution E with a concentration of 2.14 mg / mL; Solution E was quickly added to solution D, and ultrasonic emulsification was performed for 10 minutes. The ethanol and chloroform were removed by rotary evaporation for 10 minutes, and the solution was centrifuged at 5000 r / min for 5 minutes to obtain luteolin nanoparticles.
4. The method for preparing the composite hydrogel according to claim 2, characterized in that: In step S1, the viscosity of chitosan in solution A is 200-400 mPa.s, and the concentration is 200 mg / mL.
5. The method for preparing the composite hydrogel according to claim 2, characterized in that: The viscosity of the sodium alginate in the solution B in step S2 is 200-400 mPa.s, and the concentration is 200 mg / mL.
6. The method for preparing the composite hydrogel according to claim 2, characterized in that: The concentration of genipin in solution C in step S3 is 5 mg / mL.
7. The method for preparing the composite hydrogel according to claim 2, characterized in that: In step S4, the volume ratio of solution A, solution B and solution C is 5:10:
1.
8. The method for preparing the composite hydrogel according to claim 2, characterized in that: The light-proof standing temperature in the step S4 and the step S5 is both 37°C.
9. The method for preparing the composite hydrogel according to claim 2, characterized in that: The biological stem cells are mouse adipose-derived mesenchymal stem cells.
10. Use of the composite hydrogel according to any one of claims 1 to 9 in the preparation of a repair-promoting medical dressing.
Citation Information
Cited By
Fe3O4 (at) PDA-MnO2 nano material as well as preparation method and application thereof
CN119633114A